Inuit children in snow house, Cape Fullerton, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1901)
A group of Inuit children stand and sit inside a snow house at Cape Fullerton, Hudson Bay, January 6, 1901. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo #13. Number 35 is etched into emulsion on plate. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.